Inventarisasi Tanaman Araceae Di Taman Maluku Bandung, Jawa Barat - M Renald Kevin Setia Hadi; Muhammad Rafi Fauzan; Muhammad Abdan Syahida Arifin; Ateng Supriatna (Polygon : Jurnal Ilmu Komputer dan Ilmu Pengetahuan Alam, 2024)
This research aims to inventory the diversity of plants belonging to the Araceae family found in Taman Maluku, Bandung, West Java. The Araceae family is known for its diverse plants with unique characteristics that are important for the local ecosystem. The method used in this research includes field surveys. The results show that there are several species from the Araceae family distributed across various areas of Taman Maluku Bandung, with a total of 5 genera from 1 family found. This study provides important information on biodiversity in Taman Maluku and serves as a basis for conservation and sustainable management efforts in the park. These findings can also contribute to scientific knowledge about Araceae flora in tropical regions.